Mudbound [videorecording (DVD)] - Rees, Dee; Williams, Virgil; Mulligan, Carey, 1985-; Clarke, Jason, 1969-; Mitchell, Jason, 1987-; Blige, Mary J.; Morgan, Rob; Banks, Jonathan, 1947-; Hedlund, Garrett, 1985-; Jackson, Danielle Amir; Jordan, Hillary, 1963- (Criterion collection, 2024)
In the Mississippi Delta of the 1940s, two farming families one of white landholders, and one of Black tenant farmers are bound by the unforgiving soil they share as they struggle to survive amid the upheavals of World War II and the poisonous hatred of the Jim Crow South. Each family sends a young man off to battle; when they return home, scarred, and find a common bond, the community is ripped apart.